SENGKARUT DAN KETUMPULAN REGULASI PENYELESAIAN SAWIT RAKYAT DALAM KAWASAN HUTAN - Muhammad Hasan Muazis (Indonesian State Law Review, 2020)
Indonesia is the largest palm oil exporting in the world with a yield reaching USD 1,868 billion in July 2020. This condition is supported by the palm oil cover area which reaches 16.391 million hectares. However, the oil palm plantation sector still has various problems ranging from welfare, the environment, regulations, and human rights. This research will discuss about the welfare conditions of smallholder oil palm farmers in forest areas and regulations related to this issue. Basically, oil palm is Indonesia's export economic potential in the plantation sector, but in practice there is still social imbalance and various policy steps need to be taken to address this problem.